Detection, Antibiotic Susceptibility, and Selected Virulence Factors of Staphylococcus spp. Isolated from Clinical Samples in Baquba City - Alageedi, Neyaf; Samar Mutar,; Huda Abdul Hameed,; Hadeel Ahmed, (AlQalam Journal of Medical and Applied Sciences, 2025)
Staphylococcus bacteria belong to the genus Staphylococcus of the family Micrococcaceae and are Gram-positive bacteria. This study aimed to investigate the prevalence of staphylococci in clinical samples, determine their virulence factors, biofilm formation ability, and their relationship to antibiotic resistance, with a focus on the role of the icaA and icaD genes in this phenomenon. One hundred clinical samples were collected from patients at Baqubah Teaching Hospital and cultured on nutrient media to identify staphylococci using catalase and coagulase tests. Virulence factors such as hemolysis and biofilm formation were assessed, and antibiotic susceptibility was tested using the disk diffusion method and the minimum inhibitory concentration (MIC). Polymerase chain reaction (PCR) was used to detect the presence of the icaA and icaD genes. Twenty-three staphylococcal species were isolated, of which 11 were coagulase-positive and 12 were coagulase-negative. The highest percentage of isolations was from skin swabs (52.2%), followed by nasal swabs (30.4%), and then urine (17.4%). S. aureus was the most common (47.8%), followed by S. epidermidis and S. saprophyticus. 47.8% of isolates demonstrated the ability to produce beta-hemolysin, and biofilm formation rates reached 86% for S. epidermidis and 82% for S. aureus and S. saprophyticus (60%). Antibiotics such as imipenem were most effective. According to the study's findings, most bacterial isolates could form biofilms quickly, and this capacity was frequently linked to the presence of the icaA/D genes. This link was not absolute, though, because isolates that tested positive for the genes did not form biofilms, and there were no group differences that were statistically significant (P > 0.05). The results of this study confirm that biofilm formation is a major factor in increasing antibiotic resistance in staphylococcal isolates, especially in isolates containing the icaA and icaD genes associated with biofilm formation, highlighting the importance of studying these genes within infection control programs